2019
DOI: 10.1007/s12975-019-00757-0
|View full text |Cite
|
Sign up to set email alerts
|

Complement C5 Contributes to Brain Injury After Subarachnoid Hemorrhage

Abstract: Previous studies showed that complement activation is associated with poor functional outcome after aneurysmal subarachnoid hemorrhage (SAH). We investigated whether complement activation is underlying brain injury after aneurysmal SAH (n = 7) and if it is an appropriate treatment target. We investigated complement expression in brain tissue of aneurysmal SAH patients (n = 930) and studied the role of common genetic variants in C3 and C5 genes in outcome. We analyzed plasma levels (n = 229) to identify the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…[1,[3][4][5] In experimental SAH studies, treatment with complement C5 antibodies shortly after SAH reduced brain injury with approximately 40%. [13] Complement component C5 may be an important target to reduce brain injury and hereby improve outcome after aSAH. The CLASH trial is the rst phase II trial to investigate the pharmacodynamic e cacy and safety of eculizumab in aSAH patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,[3][4][5] In experimental SAH studies, treatment with complement C5 antibodies shortly after SAH reduced brain injury with approximately 40%. [13] Complement component C5 may be an important target to reduce brain injury and hereby improve outcome after aSAH. The CLASH trial is the rst phase II trial to investigate the pharmacodynamic e cacy and safety of eculizumab in aSAH patients.…”
Section: Discussionmentioning
confidence: 99%
“…We decided on repeated drug administration with a high dose of eculizumab to prevent a wash-out effect and because the C5a concentration in the cerebrospinal uid (CSF) of aSAH patients is >1400 times increased one day after ictus compared to the C5a concentration in CSF from patients with unruptured intracranial aneurysms. [13] To decrease the risk of (meningococcal) infection due to eculizumab treatment, patients in the intervention group receive prophylactic treatment with cipro oxacin during the rst 4 weeks after ictus. During the recruitment phase, after inclusion of the 6th patient, we changed our protocol based on a serious adverse event (SAE) that occurred (cerebral fungal infection in patient with external ventricular shunt).…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complement components C3a and C5a are proinflammatory anaphylatoxins that can induce vasoconstriction and activate coagulation [9][10][11], processes that have been implicated in the pathophysiology of early brain injury and delayed cerebral ischaemia [1,12]. C5specific antibodies, which prevent the formation of C5a, have been shown to reduce microglia activation and cell death by 40% in an SAH mouse model [13]. C5 antibodies (eculizumab) are already used for other inflammatory diseases such as neuromyelitis optica and myasthenia gravis [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…As this is the rst trial to investigate the use of eculizumab in aSAH patients, the effective dosing regimen for aSAH patients is unknown. In our previous study, we found that the C5a concentration in cerebrospinal uid (CSF) of aSAH patients is highly increased (>1400 times) compared to the C5a concentration in CSF from patients with unruptured intracranial aneurysms [13]. We therefore decided upon administration of a high dose of eculizumab (1200 mg) with repeated drug administration to prevent a wash-out effect.…”
Section: Introductionmentioning
confidence: 99%